Pengaruh Kegiatan Dzikir Ratib Al-Haddad Terhadap Kecerdasan Spiritual Santri Pondok Pesantren Modern Riyadhul Jannah Subang - Puja Nurmalasari; Nando Nando; Salsa Nursaidah; Ajat Saputra (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This research is motivated by the lack of optimal spiritual intelligence in students of the Riyadhul Jannah Modern Islamic Boarding School, although there are various activities that have the potential to support the development of spiritual aspects, one of which is the Ratib al-Haddad dhikr activity. This study aims to analyze the influence of Ratib Al-Haddad dhikr activities on the spiritual intelligence of students at the Riyadhul Jannah Modern Islamic Boarding School. This study uses a descriptive quantitative method. The research subjects used were some of the female students of the Riyadhul Jannah Modern Islamic Boarding School, totaling 41 students. The data collection techniques used were questionnaires and observations. While the data analysis techniques processed and analyzed using IBM Statistic SPSS 26. The results of the study showed which means that there is an influence of the Ratib Al-Haddad dhikr activity on the spiritual intelligence of students.